PENGARUH BANTUAN PANGAN NON TUNAI TERHADAP KESEJAHTERAAN KELUARGA MISKIN DI DUSUN KETALO, BANTUL - Firdha Kusuma Wardani (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
The poverty rate in Indonesia, which continues to increase every year, has a direct impact on people's welfare. Various government programs, such as the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), and Direct Cash Transfer (BLT), were launched to address this issue and improve people's welfare. This research focuses on the effect of BPNT on the welfare of poor families in Ketalo Hamlet, Gadingsari, Sanden, Bantul, Yogyakarta, using six main indicators: right target, right amount, right time, right quality, right price, and right administration. In addition, other variables such as age, type of employment, assistance, and income were also analyzed to obtain more accurate results. Research data was collected in 2021 through questionnaires and analyzed using logit regression. The results show that the variables age and assistance have no significant effect on welfare, while type of employment and income do. In addition, the 6T indicator in BPNT distribution has been achieved in accordance with the applicable provisions.